General antioxidant activity at the allotransplantation of embryonal muscle tissue in rats - Nikolaeva, O.; Petrov, S. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
Allotransplantation of embryonal tissue is one of the actual directions in modern theoretical and medical biochemistry which is developed for stimulation and restoration of functions of the organism. Allotransplantation of the embryonal tissue is considered as possible alternative to traditional conservative methods of treatment, and also as methodological basis of experimental development. The purpose of the work was to investigate the effect of allotransplantation of the embryonic femoral muscle tissue on the general antioxidant activity. For allotransplantation of the embryonal muscle tissue 2–3 weeks' embryos were used. Under ether anesthesia in aseptic conditions the animal was fixed on surgical board in dorsal decubitus, the surgery field was shaved and processed by antiseptic agent three times. The section was carried out on internal average third of hip. Femoral muscle tissue was taken from embryos and then fixed by ligature to the hip of adult rat. The wound was sewn up layer-by-layer with densely noose suture. Used allotransplantation was carried out according to surgical rules of operations on muscles. The studied indicators were determined on the first, third and seventh days after the operative intervention in donor and recipient tissues. The implantation of the formed tissue and the false operation were performed in order to rule out the effect of both the operation itself and the effect of tissue implantation, in order to detect the effect of embryonic tissue on the formed. We examined each indicator not only when implanting the embryonic tissue, but also with the false operation and implantation of the formed tissue to the formed one, and compared the indices for all these three types of intervention. The established changes in the general antioxidant activity for the third day of the study of allotransplantation of the femoral muscle tissue of the embryo indicate a significant decrease in the overall antioxidant activity in the recipient's tissue, which may be due to the breakdown of antioxidant defense, characterized by the development of free radical damage to various components of the cell and tissues, which is a syndrome of peroxidation, but by the seventh day the antioxidant systems are restored.